Morpho-Histological, Physiological and Molecular Analysis of "Truncated Leaf Syndrome" Somaclone in Tenera Oil Palm (Elaeis Guineensis Jacq.) - Habib, Sheikh Hasna (2011)
Oil palm tissue culture is important for rapid multiplication of uniform planting materials, a % of tissue culture derived oil palm seedlings lead to a somaclonal variant termed as truncated leaf syndrome (TLS). The causes of this somaclone are unknown as no extensive research has been carried out. In order to identify the causes of TLS occurrence, it is essential to know the details of the morpho-histology, nutritional status, hormonal level and the genes that are expressed or suppressed in TLS seedlings. Therefore, the objectives of this study were to investigate the morpho-histological, physiological and molecular differences in TLS seedlings in comparison to normal. The TLS and normal oil palm seedlings were obtained from FELDA Agricultural Services Sdn Bhd, Malaysia. On the basis of the percentage of TLS occurence, the nine clones were categorized into: severely effected (>70 %), moderate (40-69 %), and mild (<40 %). Stunted growth, lower vigor, curled truncated and less green leaf, fewer number of roots and smaller shoot apical meristem (SAM) were found in TLS seedlings. The severity of TLS increased as the size of the SAM decreased indicating a clear relationship between SAM size and TLS abnormality. Crinkled and undulated leaf surfaces, coalesced mesophyll cells, sunken, deformed and fewer numbers of stomata and a smaller root cap were found in TLS leaf by scanning electron microscopy. Longer epidermal cells and a depressed epidermal layer, bigger sub-epidermal cells with different shapes, loosely arranged mesophyll cells, undifferentiated leaf vascular bundle, impaired root tips, and smaller and compact SAM with defective leaf primordial at the distal end were also observed in TLS seedlings by light microscopy. Physiological analysis revealed that the levels of Boron (5.8, 5.4 and 6.1 mg/kg in severe, moderate and mild TLS respectively), Zinc (60.1 and 54.1 mg/kg in severe and moderate TLS respectively) and chlorophyll (0.49, 0.54 and 0.53 mg/g total chl in severe, moderate and mild TLS respectively) were lower and the levels of cytokinin (tZ: 10.1, tZR: 16.9, tZOG: 34.0, tZR5'MP: 15.6 and cZR5'MP: 10.3 pmol/g in severe TLS) and brassinosteroid (brasinolide: 7.5 pmol/g in severe TLS) were higher in TLS seedlings than normal. Phenotypic and morpho-histological study revealed that this abnormality might be due to smaller SAM in severe TLS palms. Therefore, to isolate the differentially expressed genes in TLS seedlings, a forward and a reverse suppressive subtractive hybridization (SSH) library were constructed for severe TLS SAM. From the suppressive SSH library, 387 and 173 transcripts were found to be up-regulated and down-regulated in severe TLS SAM respectively. The annotated 33 % and 14 % of unique genes sequences from the forward and reverse libraries, respectively, which had significant matches were further classified based on their putative functions Three transcripts pescadillo N-terminus family protein (EgPES), TLD family protein (EgTLD) and putative finger transcription factor (EgPFTF) were selected from the forward subtracted library for full-length cDNA isolation and characterization by Real-Time RT-PCR. EgPES and EgTLD are developmental related proteins and EgPFTF is a transcriptional activator. EgTLD and EgPFTF were up-regulated in severe and moderate TLS SAM but down-regulated in mild TLS SAM. EgPES was iv up-regulated in severe TLS SAM but down-regulated both in moderate and mild TLS SAM. All three transcripts were predominantly expressed in leaf and root tissues of severe TLS SAM. Functional analyses are required for better understanding of the molecular functions of these transcripts in TLS somaclone.